Optimalisasi Produktivitas Tanaman Pala (Myristica Fragrans Houtt) Melalui Aplikasi Nutrisi Tanaman Organik-Anorganik Cair - Zakarias Frans Mores Hukom; Pieter J Kunu; Abraham Talahaturuson; Jollanda Effendy; Gun Mardiatmoko (Fakultas Pertanian, Universitas Pattimura, 2023)
The objective of this study was to optimize the productivity of nutmeg (Myristica fragrans Houtt) through the application of concentration levels and frequency of liquid organic-inorganic mixed plant nutrition was carried out in the Nutmeg Garden of Hative Besar Village, Ambon Island, using a factorial complete randomized block design 3 x 2 + 1 (control, without treatment). The first factor consisted of three concentration levels, namely 1500 ppm, 3000 ppm, and 4500 ppm. The second factor consisted of two application frequencies: every two weeks and every four weeks. The sample employed in this study had an average age of 25 years. Each treatment combination was repeated three times with the total sampled 21 trees. The following yield parameter components were observed in this study: number of harvested fruits, fresh fruit weight, wet seed weight, dry seed weight, and dry mace weight. The results showed an interaction between the combination treatment of liquid organic-inorganic mixed plant nutrient concentrations and the frequency of application to the variables of fresh fruit weight, wet seed weight, dry seed weight, and dry mace weight. The variable number of fruits harvested per plant did not show an interaction effect between the concentration level and the frequency of giving liquid organic-inorganic mixed plant nutrition. Still, the best average number of fruits harvested per plant was found in the combination treatment between a concentration of 3000 ppm and a frequency of application every two weeks. The application of liquid organic-inorganic mixed plant nutrition with a concentration of 3000 ppm with a frequency of application every two weeks showed a positive response to increasing plant productivity when compared to other treatments or without the application of plant nutrients.